Pengaruh Media Tanam dan Kompos Kotoran Kambing Terhadap Pertumbuhan dan Produksi Tanaman Tomat (Solanum lycopersicum L.) - Siregar, Gunji Maulana; Amrul, Hanifah Mutia Zaida Ningrum; Hafiz, Muhammad (JURNAL AGROPLASMA, 2024)
This research was carried out at the Panca Budi University Research site in Dusun 3 Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra with an altitude of ± 500 masl. This research will be conducted from February to April 2024. This study used a factorial Randomised Group Design (RGD) with 2 factors with 16 combinations and 3 replications so that there were 48 research plots, namely: Factor one Top Soil and Husk Charcoal Planting Media with symbol (G) consists of 4 levels, namely: G0 = 100% Top Soil, G1 = 75% Top Soil + 25% Husk Charcoal, G2 = 50% Top Soil + 50% Husk Charcoal, G3 = 25% Top Soil + 75% Husk Charcoal. Factor two Goat Manure Compost with symbol (S) consists of 3 levels, namely: S0 = 0 g/polybag S1 = 275 g/polybag S2 = 375 g/polybag S3 = 475 g/polybag. The results showed that each treatment significantly affected the growth and production of tomatoes. Treatment G2 = 75% top soil + 25% husk charcoal and S2 = 375 g/polybag gave the best results on growth and production of tomatoes. Keywords: husk charcoal, goat manure, tomato, top soil